Analysis of Prospective Students' Interest and Motivation for the Sports Study Program - Pradityana, Karisdha; Sudarwo, Raden; Mudayat, Mudayat; Sapta, Andy (Program Pascasarjana Universitas Negeri Jakarta, 2025)
Higher education plays an important role in producing superior human resources, including in the field of sports. In the midst of increasing public awareness of the importance of a healthy lifestyle and the need for sports professionals, interest in sports study programs is important to study. This study aims to analyse the level of interest, motivation, and factors that influence prospective students in choosing a sports study program. The method used was a quantitative descriptive survey with 200 respondents from various provinces in Indonesia. The results showed that 66% of respondents stated that they were very interested and 34% were interested in this study program. The main reasons behind this interest include the desire to become a professional sports teacher or coach (31.34%), personal interest in sports (23.88%), and the need for sports teachers in the region (20.40%). These findings are supported by Maslow, Holland, and Expectancy-Value theories which explain that academic choices are strongly influenced by internal motivations, social values, and perceptions of future success. This study recommends that higher education institutions strengthen their promotion strategies, curriculum development, and provision of broad career prospect information to attract more potential prospective students.